Design of Temperature and Humidity Controller of Warehouse Based On Arduino - Wu, Yong; Lei, Lei; Zhang, Jian Hu; Li, Lin Tao; Zhang, Jun (IOP conference series. Earth and environmental science, 2019)
Temperature and Humidity controller of warehouse based on Arduino IDE is designed to measure and control the temperature and humidity more conveniently and easily. The controller is controlled by Arduino micro-controller, using a combination of temperature and humidity Sensor technology, Programmable Smart LCD touch-display terminal, bluetooth module communication technology and network module technology to finish the real time detection of temperature and humidity. The data of temperature and humidity were sent to networking platform by network module. User can use any browser or smart phone to read. Once unusual phenomena occur, the temperature and humidity control system is automatically activated. The controller is operated easily and at low cost, suitable for popularization. It offers some references for the application of Arduino IDE.